(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Optimal infant and young child feeding practices are crucial for improving health outcomes and reducing mortality rates among children under the age of two. However, inadequate nutrition during this critical period remains a leading cause of global malnutrition. This study assessed key indicators of infant and young child feeding practices in Ihima District, Okehi Local Government Area, Kogi State. A cross-sectional study was conducted among mothers and caregivers in Ihima District. Respondents were recruited using convenience sampling method. Data was collected on assessment of Infant and young child feeding practice using a validated semi-structured questionnaire. The interviewer-administered questionnaire obtained information on demographic characteristics, breastfeeding practices and complementary feeding practices based on WHO guidelines. Data was analyzed using descriptive statistics and Chi-square on SPSS version 21, the p-values <0.05 was considered statistically significant. Among the 116 children studied, 75% were breastfed within one hour of birth, 74.14% were exclusively breastfed, and 48.28% received pre lacteal feeding. Additionally, 32.61% of mothers of children aged 12–23 months continued breastfeeding until the child was two years old. Timely introduction of complementary foods was observed in 66.67% of children aged 6–8 months. Of the 83 children within the 6–23 months age group, 43.37% were fed from four or more food groups. Minimum meal frequency (MMF) was adequate in 57.83%, while the minimum acceptable diet (MAD) was met by 43.37% of children. This study reported good early initiation of breastfeeding and exclusive breastfeeding practices, however complementary feeding practice was sub-optimal.